A latent class analysis of a discrete choice experiment on environmental quality of the Baltic Sea - Raivonen, Leo (My University, 2020)
The standard assumption in economics is that when making decisions, individuals are assumed to maximize their welfare. The preferences of individuals vary, so that different individuals make different decisions. In this thesis heterogenous preferences of individuals for the future environmental condition of the Baltic Sea are modeled. The main goal is to study what kind of preference groups individuals can be assigned to and how the preferences are different in the groups. Additionally, the socio-demographic characteristics and environmental attitudes of the groups are assessed. To interpret the results, consumer vs citizen framework and concepts related to attribute processing and heuristics are employed. Latent class model is used to model the heterogenous preferences. I find that a 4-class model offers the best balance of fit and interpretability. The first class has highly positive coefficients for the environmental attributes and unrealistically high willingness to pay. It is named as the “Environmental” group. The second class named “Environmental and bid” has mostly positive preferences and more reasonable willingness to pay estimates than the first class. The third class has highly negative utility estimates for the attributes and is therefore named “Non-environmental”. The fourth class is named “Status quo” for the positive utility obtained from staying in the status quo state. Multinomial logit model is employed to assess the socio-demographic and attitudinal differences between the groups. Some differences in the socio-demographic characteristics are found. Results relating to the attitudes show that individuals with more negative attitudes are more likely to be in the Non-environmental or the Status quo classes. Using the citizen vs consumer framework, I argue that individuals in the Environmental class may have responded as citizens giving much higher valuations and individuals in the Environmental class as consumers. I suggest that some individuals might employ heuristics attribute non-attendance. Future research in this area using, for example, constrained latent class models and random parameter latent class model might provide further insight to the existence and effects of these anomalies.

Taloustieteessä on tyypillisesti oletettu ihmisten maksimoivan hyötyään päätöksenteon yhteydessä. Yksilöillä on kuitenkin erilaiset preferenssit, joten he tekevät myös eri valintoja. Tämän tutkielman tarkoitus on tutkia heterogeenisiä preferenssejä Itämeren tule-vaan tilaan liittyen. Tutkielman ensisijainen tavoite on tutkia minkälaisiin preferenssiryhmiin vastaajat voidaan jakaa. Lisäksi tutkin ryhmien sosiodemografisia ja asenteelli-sia eroja. Tulosten tulkintaan käytetään kuluttaja-kaupunkilainen-viitekehystä ja peuka-losääntöjen sekä vaihtoehtojen ominaisuuksien käsittelemiseen liittyviä konsepteja. Heterogeenisten preferenssien mallinnukseen käytetään latenttien luokkien mallia. Neljän luokan malli on tulkinnan ja sopivuuden kannalta sopivin. Ensimmäisellä luokal-la on vahvat posetiiviset preferenssit ympäristön parantumiselle sekä epärealistisen korkea maksuhalukkuus. Toisella luokalla on myös pääasiallisesti positiiviset ympäristöpreferenssit ja maksuhalukkuus on ensimmäistä ryhmää realistisempi. Kolmatta luokkaa kuvaa vahvasti negatiiviset preferenssit. Neljättä luokkaa kuvaa nykytilan arvostus verrattuna muutokseen. Sosiodemografisten ja asenteellisten erojen tutkimiseen käytetään multinomiaalista logistista regressiota. Sosiodemografisissa tekijöistä löydän joitain eroavaisuuksia. Asenteelliset tulokset osoittavat, että ympäristöön negatiivisesti suhtautuvat henkilöt ovat todennäköisemmin kolmannessa ja neljännessä luokassa. Kuluttaja-kaupunkilais-viitekehystä käyttäen esitän, että ensimmäisen luokan vastaajat ovat saattaneet vastata kaupunkilais-roolista antaen korkean maksuhalukkuuden ja toisen luokan kuluttaja-roolista. Joillain vastaajilla saattaa myös olla käytössä peukalosääntöjä tai he saattavat jättää joitain vaihtoehtojen ominaisuuksia käsittelemättä vertailua tehdessään. Suosittelen tulevan tutkimuksen kohdistuvan edellä mainittuihin teemoihin. Tulevassa tutkimukseen voitaisiin käyttää esimerkiksi latenttien luokkien mallia, jossa osa kertomista on kiinnitetty tai satunnaiskertoimien latenttien luokkien mallia.
Keywords: Latent class analysis, choice experiment, environmental economics, Baltic Sea